2009
DOI: 10.1186/1471-2172-10-56
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory receptor LILRB4 (ILT3) modulates antigen presenting cell phenotype and, along with LILRB2 (ILT4), is upregulated in response to Salmonella infection

Abstract: Background: Leukocyte Ig-like receptors (LILR) are a family of innate immune receptors with immunomodulatory functions. High-level expression of the receptors LILRB2 (ILT4) and LILRB4 (ILT3) is a feature of tolerogenic antigen presenting cells and has been observed in cancer and transplant situations. There are relatively few studies regarding these receptors in the context of infection and it is not yet clear how LILRB4 exerts its inhibitory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 31 publications
(42 reference statements)
3
43
1
Order By: Relevance
“…These genes belong to the leukocyte immunuglobulin-like receptor family (9) and could potentially be involved in the mediation of the IL-10 anti-inflammatory response. One study has shown that expression of LILRB2 may be increased in macrophages cultured in vitro with Salmonella Typhimurium LPS, which is contradictory with our finding (i.e., that it is downregulated with an FC of Ϫ2.0 by N. meningitidis) (10). LAIR1 has been shown to have an inhibitory potential on various immune cells with downregulation of cytokine production and inhibition of the differentiation of peripheral blood precursors and other steps of the immune response (35).…”
Section: Global Effect Of Il-10contrasting
confidence: 56%
“…These genes belong to the leukocyte immunuglobulin-like receptor family (9) and could potentially be involved in the mediation of the IL-10 anti-inflammatory response. One study has shown that expression of LILRB2 may be increased in macrophages cultured in vitro with Salmonella Typhimurium LPS, which is contradictory with our finding (i.e., that it is downregulated with an FC of Ϫ2.0 by N. meningitidis) (10). LAIR1 has been shown to have an inhibitory potential on various immune cells with downregulation of cytokine production and inhibition of the differentiation of peripheral blood precursors and other steps of the immune response (35).…”
Section: Global Effect Of Il-10contrasting
confidence: 56%
“…Ligation of LIL-RB4, one of the inhibitory receptors, led to an upregulation of IL-10 secretion by in vitro-cultured macrophages. This inhibitory cytokine may contribute to a feedback loop of LILR-mediated inhibition as it upregulates LILRB1, LIL-RB2, LILRB3, and LILRB4 on antigen-presenting cells [35][36][37]. We are now further investigating whether the expression of the LILR family participates in the intestinal inflammation in patients with inflammatory bowel diseases.…”
Section: Discussionmentioning
confidence: 92%
“…PNG ILT3 1 ILT4 1 monocytes coexpressed high levels of HLA-DR, suggesting that cells with potential inhibitory function were those that had been activated in utero. Of interest, tolerogenic APCs are known to exist in a range of maturation states, 33 with ILT3 and ILT4 expression subject to modulation by infections 34 and, in neonates, by certain prenatal exposures. 35 Furthermore, APCs from PNG compared with Australian newborns overexpressed CD80 relative to CD86, which has been associated with promotion of T H 1 rather than T H 2 responses.…”
Section: Discussionmentioning
confidence: 99%